فاعلية استخدام تراكيب كيغان من التعلم التعاوني في اتجاهات طلبة الصف العاشر نحو مادة التربية الإسلامية بدولة الإمارات العربية المتحدة: The Effect of Using Keegan Structures of Cooperative Learning on Tenth Grade Students’ Attitudes Towards Islamic Education in UAE - Al Qudah, Qusai Fathi; Bin Yussuf, Ahmad; Bin Mohd Yusoff, Mohd Yakub @ Zulkifli (Journal of Islamic Educational Research, 2022)
This study examines the effect of using Keegan's structures of cooperative learning attitudes towards Islamic education on 10th grade students in National Emirates Schools (henceforth NESs) in the UAE. A sample of (60) 10th grade students from NESs was selected and randomly distributed into two groups: experimental and control group. The experimental one studied the Divine Revelation Unit using the Keegan Structures strategy, while a control group studied the same unit using the routine method of education. The study followed the descriptive approach in the analysis. To fulfil the study objectives an educational material was prepared according to the Keegan structures strategy, and the attitudes towards Islamic Education Scale was used as well. The findings showed significant differences in the performance of students on the scale of attitudes towards the subject of Islamic education due to the method of teaching, and in favour of the experimental group after studied using Keegan's strategy. The results also indicated that there were no statistically significant differences in students' attitudes towards Islamic education due to the variables of gender and school type. In light of these results, the study recommended the necessity of activating the Keegan structures strategy in cooperative learning in teaching Islamic education, and training teachers to use it optimally.